ỨNG DỤNG THUẬT TOÁN NHÁNH CẬN ĐỂ GIẢI MỘT SỐ BÀI TOÁN TỐI ƯU LIÊN QUAN ĐẾN CHU TRÌNH HAMILTON DỰA TRÊN BÀI TOÁN TSP - Đỗ, Như An (Trường Đại học Đà Lạt, 2023)
The Traveling Salesman Problem (TSP) is the most prominent of the combinatorial optimization problems that belongs to NP-Hard. The best algorithm for solving TSP is the branch-bound algorithm with exponential-time complexity. This paper presents how to use the branch-bound algorithm to solve some of the combinatorial optimization problems related to the Hamiltonian cycle based on the TSP.